El internet y su incidencia en la conducta de los estudiantes de octavo grado de la escuela Ing. Alfonso Coronel, Catamayo 2023 - Ayala Duarte, Lauro Iván (2023)
The present research, entitled The Internet and its impact on the behavior of eighth-grade students at Ing. Alfonso Coronel School, Catamayo 2023, aims to determine the overall impact of the internet on the behavior of eighth-grade students at Ing. Alfonso Coronel School. The specific objectives are to diagnose the current reality regarding the behavior of students in 8th grade "A" and their excessive internet usage, propose an educational improvement plan to address the existing issues related to excessive internet usage among 8th-grade students, and implement the educational improvement plan to promote proper internet use among the students. The study type is descriptive with a non-experimental transectional design, adopting a mixed approach that allowed for an exploration of the impact of internet usage on students. Various methods were employed, such as analytical, synthetic, statistical, and hermeneutical approaches, with techniques including interviews and surveys. The research instrument used was a semi-structured questionnaire, and the participating population consisted of twenty students and five teachers. The procedures involved diagnosis, theoretical foundation, data tabulation, analysis, interpretation, development of discussion, and formulation of conclusions and recommendations. These steps facilitated the proposal of a plan to analyze key points related to internet usage, aligning with meaningful learning and contributing to efficient student learning development if these techniques are correctly applied. Keywords: Internet, behavior, learning, technology.